Public Service Motivation and Prosocial Rule-Breaking: An International Vignettes Study in Belgium, Germany, and the Netherlands. (June 2022) - Weißmüller, Kristina S.; De Waele, Lode; van Witteloostuijn, Arjen
We theorize that people with high Public Service Motivation (PSM) are especially prone to engage in prosocial rule-breaking (PSRB) behavior, which ultimately leads to discriminatory practices, particularly for clients associated with positive affect. We conduct an original vignette study in three countries (Belgium, Germany, and the Netherlands) with 928 observations in total. Our findings provide tentative behavioral evidence on a linear relationship between PSM and the likelihood of PSRB and a strong positive association with client likeability, which is an asymmetric relationship: Negative affect cues have a larger negative effect than positive affect cues have a positive effect on PSRB. Although our results vary across the three country studies regarding the effects of PSM, overall, the results imply that high-PSM individuals have a tendency to being more likely to engage in PSRB and that clients who are perceived as more favorable will receive a less strict application of bureaucratic rules compared to less favorable clients.